Algae Mask: Multidisciplinary exploration on material speculation. Issue 2 (1st October 2020) - Li, Kwan Queenie; Lai, Michelle Jingmin
We live in a time where masks are rewriting wearable protocol. It is critical to understand entwining narratives around masks from the notion of health and safety to a wider discourse between the masked and the mask, including opportunistic capitalism and climatic implications. How about a mask that breathes, that is made by organic raw materials? As we confront and question narratives of the new normalcy in the year of pandemic and hindsight, these frames have coalesced in a vision of the mask as an emblem for open-source eco-consciousness-functional, accessible DIY living wearables made with biomaterials. 'Algae Mask' explores the symbiosis between humans and other beings, layered as second skins; this project is driven by an ardent group of art and design practitioners across the Asia-Pacific and European regions with ongoing satellite collaborations. A related film Algae Dream, on the other hand, speculates on the prototyping process and the sleek languages of market economy to smudge the fine line between fiction and reality. Within the bricolage of source videos and original footages, motivational video mock-up and authentic presentation documentation, the video essay intends to challenge audience in a multiplicity of narrations stemming from discourses of business and science.